Cognitive Style (Field Independence-Dependence) and its Relationship to the Attention Process among Primary School Pupils. - benzetta, baldia (Journal of Social Sciences and Humanities, 2016)
The cognitive approach based on the individual's mental processing of information constitutes one of the most important entries in explaining human learning, considering that the learner actively engages with the educational content through fundamental abilities that transform this content into ideas, meanings, psychological attitudes, or motor skills. Perhaps awareness, concentration, and selection serve as the procedures that guide the learning process; these are components of the attention process that lead to memory storage and the subsequent formation of prior experiences. Despite the existence of subjective and external determinants of this mental process—which create individual differences among learners in terms of maintaining attention or suffering from distraction—the teacher faces the responsibility of first understanding these factors and, secondly, finding instructional methods that accommodate the existing differences among students. Modern trends lie in studying the cognitive dimensions of the learner, particularly their sensory and perceptual preferences. There is the auditory learner and the visual learner, as well as the student who perceives details easily and focuses on the minute features of the field (Field Independent), versus the student who does not perceive details as much as they perceive the overall whole of the stimulus (Field Dependent).